HUBUNGAN ANTARA DUKUNGAN SUAMI DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MESIANG KABUPATEN KEPULAUAN ARU MALUKU: The Relationship Between Husband's Support And Exclusive Asi Providing In The Working Area Of Mesiang Health Center, Aru Islands District, Maluku - Natalia, Cristian; Mudhawaroh (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Exclusive breastfeeding during the first six months of life has been proven to bring many health benefits to the baby and mother. Breast milk provides essential nutrients, protects against infection and can increase the baby's antibodies. Husbands have an important role in supporting the practice of exclusive breastfeeding. Support from the husband can take the form of providing accurate information about the benefits of exclusive breastfeeding, providing emotional support to the wife, and helping to overcome obstacles that may arise during the breastfeeding process. The aim of this research is to determine the relationship between husband's support and exclusive breastfeeding in the Mesiang Health Center Working Area, Aru Islands Regency, Maluku. The research method is correlation analysis with a cross sectional approach. The population used were all mothers of toddlers aged 6-12 months, totaling 43 respondents. The sample used was 38 mothers who had babies aged 6 - 12 months who were selected using simple random sampling. The data collection instrument uses a questionnaire. Chi Square statistical test. The results of the research are that there is a relationship between husband's support and exclusive breastfeeding in the Mesiang Health Center Working Area, Aru Islands Regency, Maluku, with a value of p = 0.031, p < ?, ?=0.05. The conclusion is that the social support provided by the husband to the wife will increase the mother's motivation and enthusiasm in providing exclusive breastfeeding, so that the target of exclusive breastfeeding can be achieved, and health workers can also play an important role in achieving the success of exclusive breastfeeding. Keywords: Husband's support, exclusive breastfeeding.